Preparation and application of cobalt / zinc bimetal organic framework membrane pervious to alcohol preferentially

Through the preparation of cobalt/zinc bimetallic organic frame film, competitive coordination and crosslinking technology are used to solve the problem of insufficient flux and selectivity in bioethanol separation of traditional membrane materials, and efficient ethanol recovery and separation effects are achieved.

CN119186284AActive Publication Date: 2024-12-27BEIJING UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411456334.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-27
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

Traditional membrane materials cannot simultaneously improve flux and selectivity during the separation of bioethanol, and the influence of membrane orientation and pore size on the preferential permeability of alcohols is not fully considered when designing MOF membranes, resulting in poor separation effect.

Method used

Using the preparation method of cobalt/zinc bimetallic organic frame film, hydroxycobalt salt and hydroxyzinc salt are constructed on the porous support as heterogeneous nucleation sites, and organic ligands of bimetallic sources are introduced on the surface of the support to form a competitive ligand. The membrane is positioned to expand the pore size and adjust the crystal growth direction, and combine with the crosslinked silicon-containing polymer-modified film to improve the permeability and vaporization performance of the film.

Benefits of technology

It effectively improves the preferential transmittance and separation efficiency of ethanol, enhances the selectivity and structural stability of the membrane, and significantly improves the recovery performance of bioethanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090573130000091
    Figure BDA0005090573130000091
  • Figure HDA0005090573210000011
    Figure HDA0005090573210000011
  • Figure HDA0005090573210000012
    Figure HDA0005090573210000012
Patent Text Reader

Abstract

The invention discloses preparation and application of an alcohol-permselective cobalt / zinc bimetal organic framework membrane, and belongs to the technical field of membranes. The preparation method comprises the following steps: firstly introducing hydroxyl cobalt salt and hydroxyl zinc salt on the surface of a porous carrier as heterogeneous nucleation sites of a metal organic framework (MOF) membrane, and then putting the carrier into an organic ligand precursor solution containing a bimetal source to prepare the cobalt / zinc bimetal MOF membrane with good linkage property. Competitive coordination between cobalt and zinc further enlarges the pore size of MOFs, and makes the crystal preferentially grow along the (211) crystal face. The pore diameter is enlarged, so that the permeation of ethanol molecules is facilitated, and the preferential growth of the crystal face (211) greatly exerts the hydrophobic effect of the 2-methylimidazole ligand in the MOFs, so that water molecules are prevented from entering pore channels. And the ethanol separation factors are respectively increased by 127.3% and 163.2%. And finally, gradually coating the bimetal MOF layer with a silicon-containing polymer and a curing agent solution to enhance the pervaporation performance and the stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane separation, and in particular to the preparation and application of a cobalt / zinc bimetallic organic framework membrane that preferentially permeates alcohols. Background Art

[0002] Bioethanol is an important renewable energy source that is obtained from biomass (such as corn, sugar cane, cellulose, etc.) through a fermentation process. However, during the production process, solvents and by-products hinder the metabolism of microorganisms, resulting in increased separation costs. Membrane separation technology is very suitable for the in-situ separation of bioethanol due to its advantages such as low energy consumption, simple operation and non-cytotoxicity. However, the performance of traditional membrane materials is limited and cannot improve both flux and selectivity at the same time. Therefore, it is necessary to develop and optimize new materials to improve performance.

[0003] Metal-organic frameworks (MOFs) are porous crystalline materials composed of metal ions or clusters and organic ligands. They have the characteristics of uniform pore size, high specific surface area and adsorption affinity, which makes them increasingly widely used in the field of membrane separation. 2+ or Zn 2+ ZIF-67 and ZIF-8, which are coordinated with hydrophobic 2-methylimidazole (2-MIM), are two common MOFs materials. They have shown great potential in the pervaporation separation of alcohols with preferential permeation. However, in the process of designing MOF membranes, researchers usually do not fully consider the effects of membrane orientation and pore size on the preferential permeability of alcohols. Since the kinetic diameter of ethanol molecules (0.44nm) is larger than that of water molecules (0.28nm), and the theoretical pore size of ZIF-67 and ZIF-8 (0.34nm) is smaller than the molecular kinetic diameter of ethanol. Simply increasing the pore size of MOFs may cause water and ethanol molecules to pass through the membrane at the same time, which will not only reduce the selectivity of separation, but also weaken the overall separation effect of the membrane. Therefore, while adjusting the pore size, the orientation structure of the MOF membrane must also be carefully designed. By making full use of the hydrophobic properties of the MOFs surface to prevent the permeation of some water molecules, the preferential permeability of ethanol can be effectively improved, which is crucial to improving the separation performance of the membrane.

[0004] Bimetallic organic framework membranes are prepared by introducing two different metal nodes into the MOF structure. This method can produce a synergistic effect and enhance the performance of MOF membranes, such as adsorption selectivity, film forming properties and structural stability. In the preparation of bimetallic MOF membranes, the competitive coordination between different metals can further adjust the pore size and pore structure, control the direction of crystal growth, and thus achieve the separation of specific molecules. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation and application of a cobalt / zinc bimetallic organic framework membrane with preferential alcohol permeation. First, hydroxy cobalt salt and hydroxy zinc salt are constructed on a porous carrier as heterogeneous nucleation sites, and then the carrier with the hydroxy salt layer introduced is placed in an organic ligand precursor solution containing a bimetallic source to prepare a cobalt / zinc bimetallic MOF membrane with good intergrowth and use it for alcohol permeation by pervaporation. The cobalt / zinc bimetallic produces a competitive effect on the carrier surface, which not only prompts the MOF to form defects to increase the pore size, but also guides the crystal to grow in a specific direction, thereby improving the ethanol separation efficiency.

[0006] The specific technical solutions are as follows:

[0007] A method for preparing a cobalt / zinc bimetallic organic framework membrane that preferentially permeates alcohols comprises the following steps:

[0008] Step 1: Clean the porous carrier to remove organic matter and pollutants on the surface;

[0009] Step 2: coating a mixed solution of cobalt salt and zinc salt on the surface of the porous carrier and heating the mixed solution to convert the porous carrier into a bimetallic hydroxy salt-modified porous carrier.

[0010] Step 3: placing the support modified with the bimetallic salt layer of hydroxycobalt and hydroxyzinc in step 2 in a cobalt / zinc bimetallic organic framework membrane precursor solution, and reacting at a certain temperature for a period of time to obtain a cobalt / zinc bimetallic organic framework membrane.

[0011] The method further comprises step 4, preparing a silicon-containing polymer and a curing agent solution thereof, and alternately spin-coating the two on the surface of the cobalt / zinc bimetallic organic framework membrane in step 3 and heating and cross-linking to obtain a pervaporation separation membrane.

[0012] Furthermore, the porous carrier is one of flat membranes such as alumina (AAO), polysulfone (PSF), polystyrene (PS), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), etc., and the average pore size is 200nm to 2μm.

[0013] Furthermore, in step 2, the mixed solution of cobalt salt and zinc salt for forming the bimetallic hydroxy salt modification layer is an ethanol solution of cobalt salt and zinc salt, and the cobalt salt and zinc salt are cobalt nitrate hexahydrate and zinc nitrate hexahydrate, respectively.

[0014] Furthermore, in step 2, the concentration of the metal salt is 0.1 mol / L to 10 mol / L, and the mass ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 1:1.

[0015] Furthermore, in step 2, the coating method is one of spin coating, scraper coating, and slit coating. The spin coating has a rotation speed of 1000 to 5000 rpm and a spin coating time of 20 to 100 s. The scraper coating and slit coating have a coating rate of 1 to 10 mm·s-1 The coating time is 1 to 10 seconds.

[0016] Furthermore, in step 2, the heating temperature is 80 to 150° C., and the heating time is 1 to 6 hours.

[0017] Further, in step 3, the cobalt / zinc bimetallic organic framework membrane precursor solution is a mixed solution obtained by mixing bimetallic salt solution A and ligand solution B and then standing. Bimetallic salt solution A is a solution of cobalt nitrate hexahydrate and zinc nitrate hexahydrate in methanol and water in a volume ratio of 1:4. Ligand solution B is a solution of 2-methylimidazole in methanol and water in a volume ratio of 1:4.

[0018] Furthermore, in step 3, the concentration of the bimetallic salt solution A is 0.001-0.2 mol / L, the mass ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is (0.11-9):1, preferably (0.25-1):1. The concentration of the ligand solution B is 0.1 mol / L-2 mol / L.

[0019] Furthermore, in step 3, the reaction time is 30s to 24h, and the reaction temperature is 25 to 65°C.

[0020] Further, in step 4, the silicon-containing polymer is preferably one of hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, amino-terminated polydimethylsiloxane, and polytrimethylsilyl propyne (PTMSP).

[0021] Furthermore, in step 4, the curing agent includes a cross-linking agent and a catalyst, the cross-linking agent is preferably one of tetraethyl orthosilicate, phenyltrimethoxysilane, octyltrimethoxysilane, and polymethylhydrogensiloxane, the catalyst is one of dibutyltin dilaurate, di-n-octyltin dilaurate, a platinum-containing catalyst, and a nickel-containing catalyst, and the solvent is preferably one or more of n-heptane, toluene, dichloromethane, and n-hexane.

[0022] Furthermore, in step 4, the mass concentration of the silicon-containing polymer is 1 wt.% to 30 wt.%, the mass concentration of the cross-linking agent is 10 wt.% to 30 wt.%, and the mass concentration of the catalyst is 0.0005 wt.% to 0.01 wt.%.

[0023] Furthermore, in step 4, the spin coating speed is 1000-5000 rpm, the spin coating time is 20-100 s, the heating temperature is 80-150° C., and the heating time is 20 min-4 h.

[0024] The technical solution provided by the embodiment of the present invention has the following beneficial effects:

[0025] Through the induction of hydroxycobalt and hydroxyzinc bimetallic hydroxy salts, a cobalt / zinc bimetallic organic framework membrane was successfully prepared on a porous support. The competitive coordination between cobalt and zinc metals further expanded the pore size of MOFs and caused the crystals to grow preferentially along the (211) crystal plane. The expansion of the pore size allows ethanol molecules with larger kinetic diameters to pass quickly, and the preferential growth of the (211) crystal plane can better play the hydrophobic effect of the 2-methylimidazole ligand in MOFs to prevent water molecules from directly entering the pores of MOFs, thereby achieving more efficient recovery of bioethanol from water. Finally, the surface of the membrane was modified with a cross-linked silicon-containing polymer to enhance its pervaporation performance and liquid stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] To further illustrate the technical embodiments of the present invention, a detailed description will be given below with reference to the accompanying drawings.

[0027] Figure 1 Surface and cross-sectional SEM images of the cobalt / zinc bimetallic organic framework film prepared in Example 3 of the present invention;

[0028] Figure 2 is a pore size distribution diagram of MOFs particles removed from the surface of the metal organic framework membrane prepared in Example 3 of the present invention and Comparative Example 2;

[0029] Figure 3 3 are the XRD pole figures of the (211) crystal plane and the (110) crystal plane of the metal organic framework film prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.

[0031] Example 1

[0032] Step 1: Select polyvinylidene fluoride membrane as the porous carrier with a molecular weight cutoff of 50,000 Da. Before use, the porous carrier is ultrasonically cleaned with an ethanol / water mixed solution to remove organic matter and pollutants on the surface;

[0033] Step 2: Dissolve cobalt nitrate hexahydrate and zinc nitrate hexahydrate in ethanol at a mass ratio of 1:1 to prepare a mixed solution, wherein the metal ion concentration in the solution is 0.4 mol / L. Spin-coat the prepared mixed solution onto the surface of the polyvinylidene fluoride membrane at a spin-coating speed of 3000 rpm for 60 seconds. Heat the membrane in an oven at 120°C for 3 hours to convert it into a porous carrier modified with a bimetallic hydroxy salt.

[0034] Step 3, 0.108g of cobalt nitrate hexahydrate and 0.432g of zinc nitrate hexahydrate were dissolved in a mixed solvent of 125mL of methanol and water (volume ratio 1:4) to obtain a bimetallic salt solution A. 11.35g of 2-methylimidazole was dissolved in a mixed solvent of 125mL of methanol and water (volume ratio 1:4) to obtain a ligand solution B. The metal salt solution A and the ligand solution B were mixed and allowed to stand for 10min to obtain a mixed solution, and the porous support modified with the bimetallic hydroxy salt in step 2 was immersed in the solution to grow and prepare a cobalt / zinc bimetallic organic framework membrane.

[0035] Step 4, the silicon-containing polymer is selected from vinyl polydimethylsiloxane, the cross-linking agent is selected from polydimethylhydrogensiloxane, and the catalyst is selected from a platinum-containing catalyst. First, prepare a curing agent solution of 10wt.% vinyl polydimethylsiloxane, 25wt.% polymethylhydrogensiloxane and 0.01wt.% platinum-containing catalyst, and the solvent is dichloromethane. Alternately spin-coat the surface of the cobalt / zinc bimetallic organic framework membrane prepared in step 3 and heat in an oven at 80°C for 20 minutes for cross-linking to obtain a pervaporation separation membrane, the spin-coating speed is 3000rpm, and the spin-coating time is 30s.

[0036] Example 2

[0037] The preparation method is consistent with that in Example 1, except that: Step 3, 0.216 g of cobalt nitrate hexahydrate and 0.324 g of zinc nitrate hexahydrate are dissolved in 125 mL of a mixed solvent of methanol and water (volume ratio 1:4) to obtain a bimetallic salt solution A.

[0038] Example 3

[0039] The preparation method is consistent with that in Example 1, except that: Step 3, 0.27 g of cobalt nitrate hexahydrate and 0.27 g of zinc nitrate hexahydrate are dissolved in 125 mL of a mixed solvent of methanol and water (volume ratio 1:4) to obtain a bimetallic salt solution A.

[0040] Example 4

[0041] The preparation method is consistent with that of Example 1, except that: there is no step 4.

[0042] Example 5

[0043] The preparation method is consistent with that of Example 2, except that: there is no step 4.

[0044] Example 6

[0045] The preparation method is consistent with that of Example 3, except that: there is no step 4.

[0046] Comparative Example 1

[0047] A cobalt single metal organic framework (ZIF-67) membrane was prepared. The specific preparation method is as follows:

[0048] Step 1: Select polyvinylidene fluoride membrane as the porous carrier with a molecular weight cutoff of 50,000 Da. Before use, the porous carrier is ultrasonically cleaned with an ethanol / water mixed solution to remove organic matter and pollutants on the surface;

[0049] Step 2: Dissolve cobalt nitrate hexahydrate in ethanol to prepare a solution with a metal ion concentration of 0.4 mol / L. Spin coat the prepared solution on the surface of the polyvinylidene fluoride membrane at a spin coating speed of 3000 rpm for 60 seconds. Heat the membrane in an oven at 120°C for 3 hours to convert it into a porous carrier modified with hydroxycobalt salt.

[0050] Step 3, 0.54 g of cobalt nitrate hexahydrate was dissolved in a mixed solvent of 125 mL of methanol and water (volume ratio 1:4) to obtain a metal salt solution A. 11.35 g of 2-methylimidazole was dissolved in a mixed solvent of 125 mL of methanol and water (volume ratio 1:4) to obtain a ligand solution B. The metal salt solution A and the ligand solution B were mixed and allowed to stand for 10 min to obtain a mixed solution, and the porous carrier modified with the hydroxycobalt salt in step 2 was immersed in the mixed solution to grow and prepare a ZIF-67 metal organic framework membrane.

[0051] Step 4, the silicon-containing polymer is selected from vinyl polydimethylsiloxane, the cross-linking agent is selected from polydimethylhydrogensiloxane, and the catalyst is selected from a platinum-containing catalyst. First, prepare a curing agent solution of 10wt.% vinyl polydimethylsiloxane, 25wt.% polymethylhydrogensiloxane and 0.01wt.% platinum-containing catalyst, and the solvent is dichloromethane. Alternately spin-coat the two on the surface of the ZIF-67 metal organic framework membrane prepared in step 3 and heat in an oven at 80°C for 20 minutes for cross-linking to obtain a pervaporation separation membrane, the spin-coating speed is 3000rpm, and the spin-coating time is 30s.

[0052] Comparative Example 2

[0053] A zinc single metal organic framework (ZIF-8) membrane was prepared. The specific preparation method is as follows:

[0054] The preparation method is consistent with that of Comparative Example 1, except that the cobalt nitrate hexahydrate in step 2 and step 3 is replaced by zinc nitrate hexahydrate.

[0055] Comparative Example 3

[0056] The preparation method is consistent with that of Comparative Example 1, except that: there is no step 4.

[0057] Comparative Example 4

[0058] The preparation method is consistent with that of Comparative Example 2, except that: there is no step 4.

[0059] The metal organic framework membranes of Examples 1 to 10 and Comparative Examples 1 to 4 were tested for their pervaporation alcohol permeation performance, under the following test conditions: a 5 wt.% ethanol / water system with a feed temperature of 60°C, and a membrane downstream pressure maintained below 300 Pa. The pervaporation performance of each membrane was measured three times under the same manufacturing conditions, and the average of the three tests was used as the data point.

[0060] The performance test results are shown in the following table.

[0061]

[0062] It can be seen from the table that, compared with the performance of the ZIF-67 or ZIF-8 single metal organic framework membranes prepared in Comparative Examples 1 and 2, the cobalt / zinc bimetallic organic framework membrane prepared in Example 3 has a permeation flux increased by 48.7% and 18.4%, respectively, and a separation factor increased by 24.7% and 54.2%, respectively; compared with the performance of the membranes prepared in Comparative Examples 3 and 4, the separation factor of the membrane prepared in Example 6 was increased by 127.3% and 163.2%, respectively, which greatly improved the pervaporation alcohol permeation performance of the metal organic framework membrane.

Claims

1. A method for preparing a cobalt / zinc bimetallic organic framework membrane with preferential alcohol permeability, characterized in that: The following steps are involved: Step 1: Clean the porous carrier to remove organic matter and pollutants on the surface; Step 2, coating a mixed solution of cobalt salt and zinc salt on the surface of the porous carrier and heating to convert it into a porous carrier modified with a bimetallic hydroxy salt; Step 3: placing the support modified with the bimetallic salt layer of hydroxycobalt and hydroxyzinc in step 2 in a cobalt / zinc bimetallic organic framework membrane precursor solution, and reacting at a certain temperature for a period of time to obtain a cobalt / zinc bimetallic organic framework membrane.

2. The method according to claim 1, characterized in that The method also includes step 4, preparing a silicon-containing polymer and a curing agent solution thereof, and alternately spin-coating the two on the surface of the cobalt / zinc bimetallic organic framework membrane in step 3 and heating and cross-linking to obtain a pervaporation separation membrane.

3. The method according to claim 1, characterized in that The porous carrier is one of flat membranes such as alumina (AAO), polysulfone (PSF), polystyrene (PS), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), etc., and the average pore size is 200nm to 2μm.

4. The method according to claim 1, characterized in that In step 2, the mixed solution of cobalt salt and zinc salt for forming the bimetallic hydroxy salt modification layer is an ethanol solution of cobalt salt and zinc salt, and the cobalt salt and zinc salt are cobalt nitrate hexahydrate and zinc nitrate hexahydrate, respectively; In step 2, the concentration of the metal salt is 0.1 mol / L to 10 mol / L, and the mass ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is 1:1; In step 2, the coating method is one of spin coating, scraper coating, and slit coating; the spin coating speed is 1000-5000 rpm, the spin coating time is 20-100 s; the scraper coating and slit coating coating speed is 1-10 mm·s -1 , the coating time is 1 to 10 seconds; In step 2, the heating temperature is 80 to 150° C., and the heating time is 1 to 6 hours.

5. The method according to claim 1, characterized in that In step 3, the cobalt / zinc bimetallic organic framework membrane precursor solution is a mixed solution obtained by mixing bimetallic salt solution A and ligand solution B and then standing; bimetallic salt solution A is a solution of cobalt nitrate hexahydrate and zinc nitrate hexahydrate mixed in methanol and water in a volume ratio of 1:4; ligand solution B is a solution of 2-methylimidazole mixed in methanol and water in a volume ratio of 1:

4.

6. The method according to claim 1, characterized in that In step 3, the concentration of the bimetallic salt solution A is 0.001-0.2 mol / L, and the mass ratio of cobalt nitrate hexahydrate to zinc nitrate hexahydrate is (0.11-9):1, preferably (0.25-1):1; The concentration of ligand solution B is 0.1 mol / L to 2 mol / L; The reaction time is 30s to 24h, and the reaction temperature is 25 to 65°C.

7. The method according to claim 2, characterized in that In step 4, the silicon-containing polymer is preferably one of hydroxyl-terminated polydimethylsiloxane, vinyl-terminated polydimethylsiloxane, amino-terminated polydimethylsiloxane, and polytrimethylsilyl propyne (PTMSP); In step 4, the curing agent includes a cross-linking agent and a catalyst, the cross-linking agent is preferably one of tetraethyl orthosilicate, phenyltrimethoxysilane, octyltrimethoxysilane, and polymethylhydrogensiloxane, the catalyst is one of dibutyltin dilaurate, di-n-octyltin dilaurate, a platinum-containing catalyst, and a nickel-containing catalyst, and the solvent is preferably one or more of n-heptane, toluene, dichloromethane, and n-hexane; In step 4, the mass concentration of the silicon-containing polymer is 1 wt.% to 30 wt.%, the mass concentration of the cross-linking agent is 10 wt.% to 30 wt.%, and the mass concentration of the catalyst is 0.0005 wt.% to 0.01 wt.%. In step 4, the rotation speed used for spin coating is 1000-5000 rpm, and the time used for spin coating is 20-100 s; the heating temperature is 80-150° C., and the heating time is 20 min-4 h.

8. A cobalt / zinc bimetallic organic framework membrane with preferential alcohol permeability prepared according to the method of any one of claims 1 to 7.

9. Use of the cobalt / zinc bimetallic organic framework membrane with preferential alcohol permeability prepared by the method according to any one of claims 1 to 7 as a pervaporation membrane for alcohol-water separation.

10. According to the use described in claim 9, the alcohol water is ethanol / water.

Citation Information

Patent Citations

  • Bimetallic metal organic framework thin layer and preparation method thereof

    CN109824908A

  • Method for preparing bimetallic MOF membrane by utilizing self-conversion of hydroxyl bimetallic salt and application of bimetallic MOF membrane in pervaporation separation

    CN111672341A

  • Method for preparing metal organic framework pervaporation composite membrane through hydroxyl salt induction

    CN115350591A

  • Preparation method of alcohol-permselective polymer / MOF (Metal Organic Framework) derivative composite membrane

    CN116889804A

  • Method for producing zeolitic imidazolate framework (ZIF) crystals and coatings

    EP4286334A1